Effects and molecular mechanisms of Achyranthes bidentata Blume and Cyathula officinalis K.C. Kuan in the treatment of rheumatoid arthritis - Zhang, Liu-Bo; Yan, Yu; Lian, Wen-Wen; Zhou, Wei; Xia, Cong-Yuan; He, Jun; Xu, Yuan (Frontiers in Pharmacology, 2025)
Achyranthes bidentata Blume (ABB; Chinese name: Huai Niuxi) and Cyathula officinalis K.C.Kuan (COK; Chinese name: Chuan Niuxi), two botanical drugs collectively termed “Niuxi” in traditional Chinese medicine (TCM), are widely used for rheumatoid arthritis (RA) management. This review comprehensively summarized the pharmacological mechanisms and therapeutic potential of the metabolites of ABB and COK on RA, while addressing limitations of current evidence. Of the 314 and 185 metabolites contained in ABB and COK, respectively, 22 metabolites (including Chikusetsusaponin V and chikusetsusaponin Ⅳa), showed multiple anti-RA activities. The mechanisms underlying the effects of ABB and COK with respect to the occurrence and development of RA (including inflammatory processes, immunoregulation, fibroblast-like synoviocytes, angiogenesis, oxidative stress, cartilage degradation, and bone destruction) were evaluated (Graphical Abstract). Numerous signaling pathways, such as the nuclear factor kappa-B (NF-κB), mitogen-activated protein kinase (MAPK), and phosphoinositide 3-kinase/protein kinase B (PI3K/AKT), are involved in RA. The metabolites contained in ABB and COK have significant medicinal value and potential in the treatment of RA, while in-depth mechanism studies and clinical research are warranted to support the clinical application of these metabolites.